Effects of geogrid reinforcement in low volume flexible pavement - Kim, Minkwan; Lee, Joo Hyoung (Journal of Civil Engineering and Management, 2014)
This paper presents findings of a study on geogrid reinforced flexible pavement in a low volume road through a three-dimensional finite element analysis. A mechanistic model was developed for geogrid reinforced flexible pavement. To analyze the behavior of pavement foundation, stress-dependent resilient modulus models were employed in both base and subgrade layers. The model also incorporated previous research findings to enhance the reliability of the analysis. During the analysis, comparisons were made to contrast the responses of low volume flexible pavement with and without geogrid. The results show geogrid reinforcement reduces critical pavement responses under traffic loading, such as vertical surface deflection, tensile strain in asphalt concrete, and compressive strain in subgrade. The study found up to 18% reduction of vertical strain at the top of subgrade and 68% reduction of tensile strain at the bottom of asphalt concrete. Also, geogrid provides confining stresses in the adjacent aggregate layer, which leads to surrounding layers becoming stiffer. Based on the results of this study, the placement of geogrid reinforcement on top of weak subgrade was found particularly effective compared to that on strong subgrade.First published online: 24 Oct 2013